2005
DOI: 10.1074/jbc.m410113200
|View full text |Cite
|
Sign up to set email alerts
|

Family 6 Carbohydrate Binding Modules Recognize the Non-reducing End of β-1,3-Linked Glucans by Presenting a Unique Ligand Binding Surface

Abstract: Enzymes that hydrolyze insoluble complex polysaccharide structures contain non-catalytic carbohydrate binding modules (CBMS) that play a pivotal role in the action of these enzymes against recalcitrant substrates. Family 6 CBMs (CBM6s) are distinct from other CBM families in that these protein modules contain multiple distinct ligand binding sites, a feature that makes CBM6s particularly appropriate receptors for the ␤-1,3-glucan laminarin, which displays an extended U-shaped conformation. To investigate the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 37 publications
(36 reference statements)
4
69
0
Order By: Relevance
“…This structural convergence of a carbohydrate binding motif is also quite remarkable considering that amylose and ␤-1,4-galactan possess helical structures of differing handedness and suggests that the aromatic platform is tailored more to accommodating the "tubelike" shape of the helices rather than the recognition of specific chemical groups. Consistent with this concept TmCBM41, an ␣-1,4-glucan binding CBM, did show some cross-specificity for pectic galactan (47). TmCBM61, however, showed no affinity for fragments of amylose, indicating that a polysaccharide having a helical structure with appropriate gross dimensions is a necessary condition for binding but not completely sufficient for a polysaccharide to act as a ligand for a CBM.…”
Section: Recognition Of Plant Cell Walls-tmcbm61supporting
confidence: 63%
“…This structural convergence of a carbohydrate binding motif is also quite remarkable considering that amylose and ␤-1,4-galactan possess helical structures of differing handedness and suggests that the aromatic platform is tailored more to accommodating the "tubelike" shape of the helices rather than the recognition of specific chemical groups. Consistent with this concept TmCBM41, an ␣-1,4-glucan binding CBM, did show some cross-specificity for pectic galactan (47). TmCBM61, however, showed no affinity for fragments of amylose, indicating that a polysaccharide having a helical structure with appropriate gross dimensions is a necessary condition for binding but not completely sufficient for a polysaccharide to act as a ligand for a CBM.…”
Section: Recognition Of Plant Cell Walls-tmcbm61supporting
confidence: 63%
“…It is noteworthy that on the phylogenetic tree, although XynB3, SXA, and FSUAXH1 were members of cluster A, XynB3 and SXA clustered on the same branch while FSUAXH1 was located on a different branch. Structural and thermodynamic studies on CBM6 (1,6,11,18,44,62,63) have shown that this module by itself is functionally active. It would be interesting to compare the biochemistry of a cluster A GH43 fused directly at the C terminus to a CBM6 with a typical cluster A GH43 polypeptide (GH43 module/XX domain).…”
Section: Discussionmentioning
confidence: 99%
“…7 were scored for conservation by using ConSurf (43,44) ars of xylans and cellulose (14,15). Similarily, the CBMs of laminarinase from Bacillus halodurans, and ␤-agarase from Saccharophagus degradans, specifically recognize the nonreducing terminus of their carbohydrate substrates (16,17). The current classification in the CAZy database does not include transport proteins.…”
Section: Discussionmentioning
confidence: 99%